PENGARUH MEDIA SI KOCI BERBASIS PROJECT BASED LEARNING DAN DEEP LEARNING TERHADAP KREATIVITAS, KEMANDIRIAN BELAJAR DAN PENELARAN KRITIS SISWA KELAS IV SEKOLAH DASAR - Vinda Pandhini; Bernadus Wayudi Joko Santoso; Hariyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of using Si Koci (Si Kotak Imajinasi) media on students’ creativity, learning independence, and critical reasoning in Indonesian language learning for fourth-grade elementary students. Si Koci is an instructional innovation consisting of cards representing objects, verbs, characters, and weather elements designed to stimulate students’ imaginative and higher-order thinking. This research employed a quantitative approach with a quasi-experimental design (one group pretest-posttest design). The subjects were 16 fourth-grade students from SD Negeri 2 Kunden, Blora Regency, selected through purposive sampling. The instruments included scales of creativity and learning independence, and a critical reasoning test that were tested for validity and reliability. Data were analyzed using a paired-sample t-test. The results showed that Si Koci had a significant effect on improving creativity (t = 7.823; p < 0.05), learning independence (t = 6.947; p < 0.05), and critical reasoning (t = 8.214; p < 0.05). The highest improvement occurred in critical reasoning (28.8%). These findings indicate that integrating Si Koci into Project Based Learning and Deep Learning approaches effectively enhances students’ higher-order thinking skills and supports the implementation of the Merdeka Curriculum.